Sea-level science : understanding tides, surges, tsunamis and mean sea-level changes - Pugh, David; Woodworth, Philip
"Understanding Tides, Surges, Tsunamis and Mean Sea-Level Changes Sea levels change for many reasons and on many timescales, and extreme sea levels can result in catastrophic coastal flooding, such as the Katrina storm surge in 2005 or the Sumatra tsunami in 2004. As global sea level rises, and coastal populations increase, understanding sea-level processes becomes key to plan future coastal defence effectively"--
Machine generated contents note: Preface; List of acronyms; List of symbols; 1. Introduction; 2. Observations and data reduction; 3. Tidal forces; 4. Tidal analysis and prediction; 5. Tidal dynamics; 6. Shallow water and coastal tides; 7. Storm surges, meteotsunamis and other meteorological effects on sea level; 8. Tsunamis; 9. Sea-level changes in space; 10. Mean sea-level changes in time; 11. Sea-level changes in time to do with the solid Earth; 12. Sea-level applications; 13. Sea level and life; Appendix A. The basic hydrostatic and hydrodynamic equations; Appendix B. Currents; Appendix C. High and low water times and heights; Appendix D. Theoretical tidal dynamics; Appendix E. Legal definitions in the coastal zone; Glossary; References; Index.
Keywords: Sea level; Ocean; SCIENCE / Earth Sciences / Oceanography